Excellent response of infantile orbital hemangioma to propranolol - Sendrasoa, Fandresena A (Int Med Case Rep J, 2016)
Infantile hemangiomas are the most common vascular neoplasm that present in infancy, with more than half affecting the head and neck region. Periocularly, hemangiomas may be complicated by visual loss through induction of strabismal, deprivational, or anisometropic astigmatism. We report a case of a 5-year-old girl who presented with orbital hemangioma with potential risk of visual loss who had excellent response to propranolol.